Privatizing State Universities: Capitalism and Commercialization in Indonesia's Legal Entity State Universities (PTN-BH) Policy - Rahmatia, Ashri; Fauzan, Ahmad; Sulistyowati, Tutik (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This research aims to explore the policy of Legal Entity State Universities (PTN-BH) in Indonesia using a descriptive qualitative approach and data collection techniques through literature studies. The results show that the PTN-BH policy indicates the process of privatization of state universities where the granting of autonomy to state universities leads to privatization of higher education, state universities get the opportunity to freely develop businesses to meet their needs which can be achieved through many things, one of which is that state universities have full control to regulate policies including one of which is increasing UKT fees, as a result there is segmentation of accessibility of higher education in this case PTN-BH which leads to capitalization and commercialization in the university environment.Keywords: PTN-BH, Capitalism, Commercialization.